Risk of gestational diabetes mellitus: which lifestyle parameters should be changed? - Polina Viktorovna Popova; Aleksandra Sergeevna Tkachuk; Yana Alexeevna Bolotko; Andrey Sergeevich Gerasimov; Ksenia Alexandrovna Demidova; Evgenii Anatol'evich Pustozerov; Liubov Vladimirovna Kuznetsova; Elena Nikolaevna Grineva (Сахарный диабет, 2017)
Background. Gestational diabetes mellitus (GDM) is a common complication of pregnancy. It can cause significant problems for the mother and offspring, such as caesarean delivery, birth trauma and the development of type 2 diabetes mellitus (T2DM) in the future. The identification and correction of modifiable risk factors for GDM will provide a possibility to prevent these complications. Aim. This study aimed to identify the most significant lifestyle parameters affecting the risk of developing GDM. Methods. The study included 680 pregnant women who underwent oral glucose tolerance test at 24–32 weeks of pregnancy and responded to a questionnaire comprising the following sections stratified in a semi-quantitative manner: the consumption of major food groups and drinks and the amount of physical activity and smoking before and during pregnancy. A logistic regression analysis was performed to identify lifestyle parameters that influence GDM development. GDM was diagnosed according to the IADPSG criteria. Results. GDM was diagnosed in 266 women; the other 414 women formed the control group. The most significant dietary risk factor for developing GDM was the consumption of sausage(s), dried fruits and fresh fruits. Eating sausage(s) more than thrice a week during pregnancy increased the risk of developing GDM by 2.4 times [95% confidence interval (CI), 1.5–3.8; p < 0.001] and so did the consumption of dried fruits more than thrice a week during pregnancy [odds ratio (OR), 6.5; 95% CI, 2.5–16.8; p < 0.001)] compared with the risk of GDM by less consumption of these food groups. A regular consumption of fresh fruits more than 12 times a week during pregnancy reduced the risk of GDM (OR, 0.5; 95% CI, 0.3–0.8; p = 0.015). The habit of climbing at least four floors per day during pregnancy also reduced the risk of GDM (OR, 0.7; 95% CI, 0.5–1.0; p = 0.069). Conclusions. The recommendations for GDM prevention should include limiting the consumption of sausage(s) and dried fruits, increasing the consumption of fresh fruits and introducing regular physical activities, such as climbing stairs.